Dosimetric comparison of advanced radiotherapy approaches using photon techniques and particle therapy in the postoperative management of thymoma - Häfner, Matthias; Verma, Vivek; Bougatf, Nina; Mielke, Thomas; Tonndorf-Martini, Eric; König, Laila; Uhlmann, Lorenz; Eichhorn, Florian; Winter, Hauke; Grosch, Heidrun; Haberer, Thomas; Herfarth, Klaus; et al. (Acta oncologica, 2018)
Background: The purpose of this study was to compare dosimetric differences related to target volume and organs-at-risk (OAR) using 3D-conformal radiotherapy (3DCRT), volumetric modulated arc therapy (VMAT), TomoTherapy (Tomo), proton radiotherapy (PRT), and carbon ion radiotherapy (CIRT) as part of postoperative thymoma irradiation.Material and methods: This single-institutional analysis included 10 consecutive patients treated with adjuvant radiotherapy between December 2013 and September 2016. CT-datasets and respective RT-structures were anonymized and plans for all investigated RT modalities (3DCRT, VMAT, Tomo, PRT, CIRT) were optimized for a total dose of 50 Gy in 25 fractions. Comparisons between target volume and OAR dosimetric parameters were performed using the Wilcoxon rank-sum test.Results: The best target volume coverage (mean PTV V95% for all patients) was observed for Tomo (97.9%), PRT (97.6%), and CIRT (96.6%) followed by VMAT (85.4%) and 3DCRT (74.7%). PRT and CIRT both significantly reduced mean doses to the lungs, breasts, heart, and esophagus, as well as the spinal cord maximum dose compared with photon modalities. Among photon-based techniques, VMAT showed improved OAR sparing over 3DCRT. Tomo was associated with considerable low-dose exposure to the lungs, breasts, and heart.Conclusions: Particle radiotherapy (PRT, CIRT) showed superior OAR sparing and optimal target volume coverage. The observed dosimetric advantages are expected to reduce toxicity rates. However, their clinical impact must be investigated prospectively.